Coupling GPS with accelerometer to measure physical activity - Rosli, Mohd Hafiz; Baharuldin, Mohamad Taufik Hidayat; Abdullah, Muhammad Nazrul Hakim; Omar Fauzee, Mohd Sofian; Adam, Yunus; Yaacob, Azhar (Elsevier, 2013)
Measuring and assessing physical activity is essential to determine the quality of certain activity toward human health. This study is to test the combination of Global Positioning System (GPS) with heart rate monitor and accelerometer in determining levels of moderate to vigorous physical activity among university students during their own capability in limited time. 10 male university students (age: 20.7years± 0.82SD) participate in this pilot study. Two different jogging courses used in this physical activity study. Participants were asked to wear GPS watch with chest-strapped heart rate monitor and accelerometer before starting their activity. They were then were asked to exercise (stretching, slow jogging, brisk walking and running) freely according to their own capability in 90 minutes. Data gathered from the devices are process and analyze in specific software. A minimum of 153 kCal used in this 90 minutes activity and maximum used energy is 263.64 kCal. The respondent's movement during exercise from GPS were able to be map and viewed graphically for better analysis. Results suggested, these two devices can be combined to objectively assess physical activity.